Glucosinolates from Seed-Press Cake of Camelina sativa (L.) Crantz Extend Yeast Chronological Lifespan by Modulating Carbon Metabolism and Respiration - Francesco Abbiati; Ivan Orlandi; Stefania Pagliari; Luca Campone; Marina Vai (Antioxidants)
Glucosinolates (GSLs) are nitrogen/sulfur-containing glycosides widely present in the order of Brassicales, particularly in the Brassicaceae family. Camelina (Camelina sativa (L.) Crantz) is an oilseed plant belonging to this family. Its seeds, in addition to a distinctive fatty acid composition, contain three aliphatic GSLs: glucoarabin, glucocamelinin, and homoglucocamelinin. Our study explored the impact of these GSLs purified from Camelina press cake, a by-product of Camelina oil production, on yeast chronological aging, which is the established model for simulating the aging of post-mitotic quiescent mammalian cells. Supplementing yeast cells with GSLs extends the chronological lifespan (CLS) in a dose-dependent manner. This enhancement relies on an improved mitochondrial respiration efficiency, resulting in a drastic decrease of superoxide anion levels and an increase in ATP production. Furthermore, GSL supplementation affects carbon metabolism. In particular, GSLs support the pro-longevity preservation of TCA cycle enzymatic activities and enhanced glycerol catabolism. These changes contribute positively to the phosphorylating respiration and to an increase in trehalose storage: both of which are longevity-promoting prerequisites.